Systematic review and meta-analysis of PIT tagging effects on mortality and growth of juvenile salmonids - Knut Wiik Vollset; Robert J. Lennox; Eva B. Thorstad; Samuel Auer; Kerstin Bär; Martin H. Larsen; Shad Mahlum; Joacim Näslund; Henrik Stryhn; Ian Dohoo (Reviews in Fish Biology and Fisheries, 2020)
A systematic review and meta-analysis was conducted to evaluate the appropriate tag:fish size ratio when tagging juvenile salmonids (genera Oncorhynchus , Salmo , and Salvelinus ). The review yielded 18 publications with 211 control and treatment groups reporting results from laboratory studies on the effects of passive integrated transponder (PIT) tags, plus a small number of additional studies on acoustic transmitters. A meta-analysis of the PIT tagging studies showed significant heterogeneity among studies with respect to mortality. Meta-regression revealed that juvenile salmonid mortality increased curvilinearly with the tag:fish length ratio, indicating that mortality risk is rapidly enhanced as smaller fish or larger tag sizes are used. The tag:fish length ratio effect on daily length or mass gain increased linearly. The results provide an estimate of the effects of the tag:fish length ratio on mortality and growth parameters in juvenile salmonids. Based on this, we suggest that researchers can follow best practices for tagging juvenile salmonids with tags that are not greater than 17.5% of fish total length (TL). This equates a minimum size threshold of 131 mm TL for tagging salmonids with 23-mm PIT tags, and 69 mm TL with 12-mm PIT tags. This information can assist researchers, managers, and welfare agencies striving to use the best possible evidence to make informed decisions regarding fish tagging.